Self-directed learning readiness and online learning self-efficacy among undergraduate nursing students - Rawhia Salah Dogham; Nermine M. Elcokany; Asmaa Saber Ghaly; Thoraya Mohamed Abdelaziz Dawood; Fahad M Aldakheel; Maria Blesilda B. Llaguno; Dalia M. Mohsen (Elsevier, 2022)
Background: Self-efficacy is a key aspect to succeed in both online learning and self-directed learning readiness. Self-directed learning is described as learning on one's initiative, with the learner taking major responsibility for the effort's design, implementation, and evaluation. Aim: Assess the relationship between self-directed learning readiness and online learning self-efficacy among undergraduate nursing students in Saudi Arabia. Methods: A correlational descriptive research design among 282 nursing students from 3 selected nursing colleges in Saudi Arabia. One tool was developed includes self-directed learning readiness scale and online learning self-efficacy. Findings: The over-all mean score online learning self-efficacy of the students was 5.21 ± 1.26 which represents an expert. 39.4 % of the students show Above-average SDL readiness. There is a significant positive correlation between self-directed learning readiness and overall online learning self-efficacy (r = 0.641, p = 0.00*). Conclusion: The majority students' self-directed learning readiness ranges between the average and above the average. The significant relationship between the two scales addresses how self-efficacy is an essential part of self-directed learning readiness.